2020
DOI: 10.3762/bjoc.16.209
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and electrochemical study of tailor-made crown ethers for redox-switchable (pseudo)rotaxanes

Abstract: Crown ethers are common building blocks in supramolecular chemistry and are frequently applied as cation sensors or as subunits in synthetic molecular machines. Developing switchable and specifically designed crown ethers enables the implementation of function into molecular assemblies. Seven tailor-made redox-active crown ethers incorporating tetrathiafulvalene (TTF) or naphthalene diimide (NDI) as redox-switchable building blocks are described with regard to their potential to form redox-switchable rotaxanes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
(139 reference statements)
0
11
0
Order By: Relevance
“…For NDIC7 we obtained a crystal structure (ESI † section 8). In the crystal, the dihedral angle between the phenyl group and the NDI is 70.01(11)°, which is considerably flatter than for NDIC8 45 (84.18(8)°), in order to facilitate π-π interactions between the NDIs of neighbouring NDIC7 in the solid state. The ring sizes of NDIC8, NDIC7 and TTFC8 are wider than those of DBC8 and BC7, respectively, as the 4.766( 6) Å (NDIC7) / 4.730(4) Å (NDIC8) distance of the two phenolic O atoms in the NDI-substituted macrocycles as well as the S-S distance of 3.3136(13) Å in TTFC8 46 are substantially larger than the O-O distance of 2.5642(5) Å in DBC8.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 87%
See 2 more Smart Citations
“…For NDIC7 we obtained a crystal structure (ESI † section 8). In the crystal, the dihedral angle between the phenyl group and the NDI is 70.01(11)°, which is considerably flatter than for NDIC8 45 (84.18(8)°), in order to facilitate π-π interactions between the NDIs of neighbouring NDIC7 in the solid state. The ring sizes of NDIC8, NDIC7 and TTFC8 are wider than those of DBC8 and BC7, respectively, as the 4.766( 6) Å (NDIC7) / 4.730(4) Å (NDIC8) distance of the two phenolic O atoms in the NDI-substituted macrocycles as well as the S-S distance of 3.3136(13) Å in TTFC8 46 are substantially larger than the O-O distance of 2.5642(5) Å in DBC8.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 87%
“…15 In a study on TTFand NDI-decorated crown ethers with different cavity sizes, crown [8] ethers revealed a preference for dibenzylammonium and crown [7] wheels for benzyl alkyl ammonium stations, suggesting integrative self-sorting for more functional wheels. 45 Herein, we propose a blueprint to sequence-sorted heterocircuit [3]rotaxanes using one directional axle and a library of five macrocycles carrying three different types of functional units. This approach allows for unrestricted selection and combination of the functional units in rotaxane structure.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Recently, we have shown that the spectroelectrochemical properties of redox-active crown ethers are not significantly influenced by the crown ether size. 45 This allows us to use the crown ether sizes to program the position of the functional unit on the axle without changing the spectroelectrochemical properties of the functional units. Therefore, the hetero [3]rotaxane combinations carrying DBC8 / NDIC7 and NDIC8 / BC7 are considered as "sequence pseudoisomers".…”
Section: Design Of Molecular Building Blocksmentioning
confidence: 99%
“…15 In a study on TTF-and NDI-decorated crown ethers with different cavity sizes, crown [8] ethers revealed a preference for dibenzylammonium and crown [7] wheels for benzyl alkyl ammonium stations, suggesting integrative self-sorting for more functional wheels. 45 Fig. 1 Schematic representation of [2] and [3]rotaxanes containing a directional axle (dark blue) and one or two macrocycles (grey) carrying functional units (orange and green).…”
Section: Introductionmentioning
confidence: 99%